PENGARUH KUALITAS PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL TERHADAP KEPUASAN MASYARAKAT DELI SERDANG - Dian Artika; Indah Patmawati; Venny Handayani; Mohammad Irfan Al Qohirie (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This research aims to analyze the influence of public service quality on community satisfaction at the Population and Civil Registration Office of Deli Serdang Regency. This research uses a qualitative approach with a literature study method sourced from various journals and scientific articles relevant to the research topic. The data is analyzed using qualitative descriptive analysis techniques by reviewing and comparing previous research findings. The analysis results show that the quality of public services affects the level of community satisfaction in population administration services. Some members of the public have expressed sufficient satisfaction with the services provided, particularly in the processing of civil registration documents such as Family Cards and e-ID cards. However, there are still several obstacles such as the timeliness of service, clarity of procedures, and limited service facilities. Therefore, the improvement of public service quality needs to be continuously carried out to enhance public satisfaction with population administration services.